2021
DOI: 10.3390/ejihpe11030051
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at the Emotional Intelligence Construct: How Do Emotional Intelligence Facets Relate to Life Satisfaction in Students Involved in Bullying and Cyberbullying?

Abstract: Adolescents’ perception of their own emotional abilities has been related to psychological adjustment and well-being. However, there are still few studies focusing on specific emotional dimensions in relation to bullying and well-being in adolescence. This study analysed the relationship between emotional intelligence (EI) facets, satisfaction with life, bullying and cyberbullying in adolescents. The sample consisted of 3520 high school students (51.5% females) aged between 12 and 18 years (M = 14.37; SD = 1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
0
10
0
1
Order By: Relevance
“…Studies reveal that not all students who are targeted end up developing adverse outcomes (Greene et al, 2014) and that protective factors such as family support (Miranda et al, 2019), emotional intelligence (Quintana-Orts et al, 2021), schoolwork-related anxiety (Huang, 2020), and psychological capitals (Cassidy et al, 2014) help students better cope with their victimization experiences. Even though school plays a major role in children's everyday life, particularly in relation to peer victimization (Hong & Espelage, 2012), little research has explored the role of the school environment in explaining the mechanism that underlies the relationship between victimization and life satisfaction (Huang, 2020).…”
mentioning
confidence: 99%
“…Studies reveal that not all students who are targeted end up developing adverse outcomes (Greene et al, 2014) and that protective factors such as family support (Miranda et al, 2019), emotional intelligence (Quintana-Orts et al, 2021), schoolwork-related anxiety (Huang, 2020), and psychological capitals (Cassidy et al, 2014) help students better cope with their victimization experiences. Even though school plays a major role in children's everyday life, particularly in relation to peer victimization (Hong & Espelage, 2012), little research has explored the role of the school environment in explaining the mechanism that underlies the relationship between victimization and life satisfaction (Huang, 2020).…”
mentioning
confidence: 99%
“…In general, better emotional management skills are associated with life satisfaction and better psychological adjustment. The results showed that adolescents with high emotional understanding were able to cope with stress better, while adolescents with low levels of emotional regulation showed social anxiety and more symptoms of stress, low self-esteem, depression, low life satisfaction, risk of suicide [5,16,19,23]. Emotional intelligence component consists of the capability to assess one's own, others, use and regulate emotions [16].…”
Section: Personal Resourcesmentioning
confidence: 99%
“…This is a global phenomenon and an ongoing trend across all continents. Numerous studies, such as Lomas et al (2012), andQuintana-Orts et al (2021), investigated the relation between bulling and the lack of EI on the victim, as well as the aggressor. Through this research, the authors attempt to reinforce the positive effects of EI in our daily lives and urge authorities to incorporate EI training permanently into the curricula.…”
Section: Introductionmentioning
confidence: 99%